Letter to the editor: Inappropriate use of urinary catheter and its common complications in different hospital wards - Kamarulzaman, Mohd Nazli (Saudi Center for Organ Transplantation, 2013)
I read with great interest the article entitled "Inappropriate use of urinary catheter and its common complication in different hospital wards" by Davoodian et al. Their report is very informative, with some insight into the current trend of usage of indwelling urinary catheters (IUCs). However, their classification of urinary tract infection (UTI) is not precise. [1] The authors did not elaborate which classification of UTI they have used. Moreover, they also did not identify whether the patient had symptomatic UTI or asymptomatic UTI. In other studies, this definition of UTI was clearly stated in the methodology, and thus the end result of the study was able to determine whether the patients had symptomatic UTI or only bacteriuria. In an earlier study, Leone et al found that majority of the patients were asymptomatic and only 7.7% (15/194) of the patients developed symptomatic UTI. [2]